Detection of codeine and fentanyl in saliva, blood plasma and whole blood in 5-minutes using a SERS flow-separation strip. Issue 18 (19th August 2019) - Shende, Chetan; Brouillette, Carl; Farquharson, Stuart
Abstract : A rudimentary flow strip, based on SERS, was developed and used to measure drugs, such as fentanyl, in saliva, plasma, and blood. Fully developed, the strip could be used with hand-held Raman spectrometers as a simple, point-of-care drug analyzer. Abstract : A simple-to-use device to measure drugs in saliva, blood plasma, and whole blood for point-of-care analysis and treatment of overdose patients has been investigated. A rudimentary flow strip has been developed to separate opioids from these biofluids for analysis by surface-enhanced Raman spectroscopy (SERS). The strips are based on lateral flow assays, in which the antibodies have been substituted by SERS-active pads for detection. Samples of codeine and fentanyl, artificially added to these biofluids, were measured using the strips by a field-usable Raman spectrometer. We report measurement of these drugs in these biofluids from 0.5 to 5 μg mL −1 in 5 minutes. Calculated limits of detection for the spectra suggest that these drugs could be measured at 5 to 20 ng mL −1 with improvements in the strips' separation capability.